Timothy Akis bei der Eröffnung seiner ersten Ausstellung im Jahr 1969. Mit Prof. Ralph Bulmer (links) und Dr. John Gunther (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1969)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Artists; Painting; Exhibitions; Photographs; Art Exhibition; Papua New Guinea; New Guinea